Antibacterial Activity of Semi Purified Extract of Marine-Derived Trichoderma reesei PDSP 5.7 Using Bioguided Fractionation Method - Mada Triandala Sibero; Nunung Febriany Sitepu; Tao Zhou; Yasuhiro Igarashi (Universitas Diponegoro, 2020)
Bioguided fractionation method is commonly used to obtained targeted fraction with certain biological activity. In this study, bioguided fractionation method using HPLC was applied to obtained antibacterial fractions from marine-derived fungus Trichoderma reesei PDSP 5.7. The result shows that fraction from mycelium and medium extract had antibacterial activity against ESBL E. coli and S. enterica ser. Typhi with a range of inhibition zone was 1.35±0.15 to 8.82±0.22 mm2. From 32 fractions of each extract, the mycelial extract had 7 active fractions, 3 active fractions from broth medium which extracted using 1-butanol and 5 active fractions from ethyl acetate extract. This study indicated that crude extract of fungus T. reesei PDSP 5.7 was more potential as the source of antibacterial agents rather than the crude extract that obtained from its broth medium.